1992
DOI: 10.1037/0021-843x.101.3.460
|View full text |Cite
|
Sign up to set email alerts
|

Panic attacks in the nonclinical population: An empirical approach to case identification.

Abstract: Although self-reports of panic attacks are common among student populations, it is not clear that their panic experiences are actually comparable to those of patients with clinical anxiety disorders. An empirical approach was taken to this problem by using a cluster analysis procedure to identify subjects within two samples of university students who reported panic attack symptom profiles that resembled those of patients with panic disorder. Such empirically defined "clinical" panic attacks were reported by 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…In the NCS-R, Kessler et al (2006) found a lifetime prevalence rate of 22.7% and a past-year prevalence rate of 11.5% for the experience of panic attacks, and other studies have found even higher past-year prevalence rates. For example, within a large sample of undergraduate students (n = 805; a population consistent with that studied here), Wilson et al (1992) found that 33.4% had experienced a non-clinical panic attack in the past year.…”
mentioning
confidence: 90%
“…In the NCS-R, Kessler et al (2006) found a lifetime prevalence rate of 22.7% and a past-year prevalence rate of 11.5% for the experience of panic attacks, and other studies have found even higher past-year prevalence rates. For example, within a large sample of undergraduate students (n = 805; a population consistent with that studied here), Wilson et al (1992) found that 33.4% had experienced a non-clinical panic attack in the past year.…”
mentioning
confidence: 90%
“…Although the measures used in this study have been found, for the most part, to be reliable and valid for their intended purposes, more work is needed. In particular, more research is needed on the reliability and validity of the Panic Attack Questionnaire (see Cash, 1989, andWilson et al, 1991). Although the questionnaire has been used in several adult studies, it has been used less frequently with adolescents (cf.…”
Section: Sig Direct Effectmentioning
confidence: 99%
“…Patients with more comorbidity are, by definition, held to a higher standard since to attain "remission" they must improve on a greater number of dimensions than individuals with less comorbidity. An unresolved problem in defining remission as the total absence of any symptoms is that panic attacks occur in a certain proportion of "normal" (i.e., nonclinical) individuals (Wilson et al, 1992) so that finding the proper threshold to define clinical significance is difficult Besides variability in the type of criteria used to measure outcome, outcome has almost uniformly been conceptualized in a cross-sectional as opposed to longitudinal fashion. Few studies have attempted to measure fluctuations in symptoms over time so that questions about whether panic disorder, like depression, may have some degree of periodicity, have been infrequently explored (Gurguis et al, 1988;Geraci and Uhde, 1992).…”
Section: Outcome Criteriamentioning
confidence: 99%